IMPLEMENTASI KEBIJAKAN MODEL KAMPUNG KONSERVASI TAMAN NASIONAL - Pratidina, Ginung (Jurnal Ilmu Administrasi Negara, 2013)
Thisstudy aims to determine the model of policy implementation hometown conversion Hazy SalakMountain National Park in kelestaria environmental improvement and welfare of the community. Locations were taken in two villages namely indigenous villages and rural villages Kesepuhanregular administration Sukagalih village . Using research methods research study participationaction , where the data obtained with the aim of finding problems with new measures to solveproblems , and improve the employment situation . Data were collected from 30 imforman consistof the officers involved in the management and villagers elected GHSNP . Analysis of the datathrough qualitative analysis of the data obtained by the method of workshops , focus groups anddiaries ( log book ) . The results showed that the implementation of policies Conversion ModelKampung Salak Mountain National Park (MKK GHSNP) in improving the forest environmentand the welfare of society has not been effective . The main factor is the cause for differencesin the perception of the cultural values of the two communities on the concept of sample MKK.Keywords: policy implementation , conservation , reforestation , rehabilitation , participatoryobservation.